Therapeutic Success of Tiotropium/Olodaterol, Measured Using the Clinical COPD Questionnaire (CCQ), in Routine Clinical Practice: A Multinational Non-Interventional Study - Valipour, Arschang; Avdeev, Sergey; Barczyk, Adam; Bayer, Valentina; Fridlender, Zvi; Georgieva, Mariela; Kudela, Ondřej; Medvedchikov, Alexey; Miron, Ramona; Sanzharovskaya, Maria; Šileikienė, Virginija; Šorli, Jurij; et al. (International journal of chronic obstructive pulmonary disease, 2021)
BACKGROUND: The Clinical COPD Questionnaire (CCQ) is a simple patient-reported tool to measure clinical control of chronic obstructive pulmonary disease (COPD). OBJECTIVE: This open-label, single-arm, non-interventional study (NCT03663569) investigated changes in CCQ score during treatment with tiotropium/olodaterol in clinical practice. METHODS: Data were included from consenting COPD patients, enrolled in Bulgaria, Czech Republic, Hungary, Israel, Lithuania, Poland, Romania, Russia, Slovenia, Switzerland and Ukraine, who were receiving a new prescription for tiotropium/olodaterol according to the treating physician in a real-world environment. The primary endpoint was the occurrence of therapeutic success, defined as a 0.4-point decrease in CCQ score after treatment with tiotropium/olodaterol for approximately 6 weeks. RESULTS: Overall, 4819 patients were treated; baseline and Week 6 CCQ scores were available for 4700 patients, mostly classified as Global Initiative for Chronic Obstructive Lung Disease (GOLD) B (51.6%) or D (42.7%). After 6 weeks' treatment, 81.4% (95% confidence interval [95% CI] 80.24-82.49) of patients achieved therapeutic success; mean improvement in overall CCQ score was 1.02 points (95% CI 1.00-1.05). Improved CCQ score was seen in 92.2% of patients (95% CI 91.43-92.98), 2.5% had no change and 5.3% showed a worsening. When stratified by prior treatment, the greatest benefit was seen in treatment-naïve patients, with 85.7% achieving therapeutic success, compared with 79.5% of those pretreated with long-acting β2-agonist (LABA)/inhaled corticosteroid (ICS) and 74.2% of those pretreated with LABA or long-acting muscarinic antagonist (LAMA) monotherapy. Overall, rescue medication decreased by 1.25 puffs/day (95% CI 1.19-1.31) versus baseline. In total, 29 patients (0.6%) reported drug-related adverse events and 7 patients reported serious adverse events (0.15%). CONCLUSION: In 4700 COPD patients, 6 weeks' treatment with tiotropium/olodaterol, as initial treatment or follow-up to LAMA or LABA monotherapy or LABA/ICS, improved CCQ and decreased rescue medication use. The adverse event profile was consistent with the known safety profile of tiotropium/olodaterol.
Keywords: Surveys and Questionnaires; Humans; Administration, Inhalation; fixní kombinace léků; COPD; tiotropium; Polsko; Bronchodilator Agents; výsledek terapie; lidé; antagonisté muskarinových receptorů; Švýcarsko; agonisté beta-2-adrenergních receptorů; Hungary; Poland; non-interventional study; Rumunsko; tiotropium bromid; Benzoxazines; Muscarinic Antagonists; průzkumy a dotazníky; Izrael; Maďarsko; Adrenergic beta-2 Receptor Agonists; Bulgaria; CCQ; Romania; Tiotropium Bromide; Switzerland; benzoxaziny; Treatment Outcome; Czech Republic; Clinical COPD Questionnaire; Rusko; chronická obstrukční plicní nemoc; aplikace inhalační; Russia; Pulmonary Disease, Chronic Obstructive; Bulharsko; Česká republika; Drug Combinations; Israel; bronchodilatancia; olodaterol